Family-Managed Home Care in Ontario for Families with Technology-Dependent Children - Fulton, Andrea (My University, 2022)
Background: Advances in technology have led to an increasing number of CMC-technology dependent children being discharged from hospital to their home communities. Families with CMC-technology dependent children require home care nursing services established prior to discharge. The Family-Managed Home Care model is used by some families to acquire these nursing services. Aim: The study purpose was to explore how families with CMC-technology dependent children describe their use of and experiences with using the Family-Managed Home Care model to coordinate nursing care. Methods: Thorne’s interpretive description method was used. Virtual, in-depth, semi-structured interviews were conducted with nine parents of CMC-technology dependent children. Data was analyzed using Braun and Clarke’s reflexive thematic analysis. Results: Parents of CMC-technology dependent children using the Family-Managed Home Care model became their child’s care manager. The process of managing the child’s care occurs in three interrelated and overlapping phases: (1) transitioning home, (2) building the home care team, and (3) partnering to provide care. Control was identified as a central concept that underpinned each step in the overarching process of managing the child’s care. Parents value the control provided by the Family-Managed Home Care model as this alleviated some stress, anxiety, and uncertainty in caring for a CMC-technology dependent child at home. Conclusion: Parents using this model of home care require enhanced support from LHINs and health care providers. Increasing health care provider knowledge of the Family-Managed Home Care model is needed to further support parents. Improved organization of discharges and policy changes are needed.
Family-Managed Home Care
Keywords: family-managed home care; technology-dependent children; home care nursing